Metabolic pattern formation in the tumor microenvironment - Ziwei Dai; Jason W Locasale (Molecular Systems Biology)
Abstract Metabolic alterations including increased glycolysis are a common feature of many cancers. In their recent study, Lowengrub, Waterman, and colleagues (Lee et al, 2017) report a spatial pattern of glycolysis in solid tumors that occurs within the tumor microenvironment. This spatial organization is linked to gradients derived from Wnt signaling and nutrient availability that mediate a reaction‐diffusion mechanism and is consistent with a Turing‐type model of spatial localization.